Perencanaan Penerangan Jalan Umum Menggunakan Pembangkit Listrik Tenaga Surya Pada Jalan Ir. H. Nusyirwan Ismail, M.Si Di Kecamatan Samarinda Ulu, Kota Samarinda: Indonesia - Rizky Aprylianto Susilo (J-ENSITEC, 2023)
This study discusses the Planning of Public Street Lighting Using a Solar Power Plant (PLTS) on Jalan Ir.H.Nusyirwan Ismail, M.Si in Samarinda District, Ulu Samarinda City. Jalan Nusyirwan Ismail has a road length of 5600 meters and a road width of 7 meters. Based on the road layout and calculations, the total number of poles used is 141 poles with a total of 282 light points used. In planning public street lights using solar power on the Nusyirwan Ismail street, the PJUTS used is the All In One PJUTS type, which has advantages in terms of economy, security, and better reliability than using conventional PJUTS.